THE USE OF “TRANSPORTATION SONG” IN TEACHING VOCABULARY - Nur Haira; Renda Zelkasih; Putri Amanda (Perkumpulan Madani Publisher Indonesia, 2025)
The purpose of this study is to investigate how transportation songs are used to teach vocabulary in English, with a focus on how they affect students' motivation to learn. This study uses observational methods to gather relevant data, with research objectives centered on the usage of transportation music to boost motivation among learners and their impact on topic learning. The utilization of the observation method allowed for the observation of interactions between teachers and students when songs were being taught.Students' emotional reactions, degree of engagement, and shifts in their drive to study are among the data gathered. To analyze the data, trends in the interactions between the teacher and students as well as shifts in the learning motivation of the students before, during, and after the use of transportation songs in the classroom were noted. The results of this study show that students' motivation to learn is significantly impacted when transportation songs are used to teach skills. The findings of the observations indicated that when transportation songs were incorporated into vocabulary lessons, students' engagement levels increased and they exhibited positive emotional reactions. Furthermore, this study demonstrates how teaching with transport music can positively impact students' enthusiasm to learn. This research's practical implication is that music-related teaching and learning tactics, such using transit songs to get students more motivated and involved in vocabulary learning, can enhance instruction.